Billionaires : the lives of the rich and powerful - Cunningham, Darryl (Drawn & Quarterly, 2021)
"In Billionaires, Darryl Cunningham offers an illuminating analysis of the origins and ideological evolutions of four key players in the American private sector--Amazon founder and CEO Jeff Bezos, media mogul Rupert Murdoch, and oil and gas tycoons Charles and David Koch. What emerges is a vital critique of American capitalism and the power these individuals have to assert a corrupting influence on policy-making, political campaigns, and society writ large... In criticizing the uncontrolled reach of power by Rupert Murdoch (in fueling the far right), the Koch Brothers (in advocating for climate change denial), and Jeff Bezos (in creating unsafe working conditions), Cunningham speaks truth to power. Billionaires ends by suggesting alternatives for a safer and more just society."--